Vlog as Learning Media to Train English Fluency and Public Speaking Skill - Mufidah, Zakiyatul; Roifah, Miftahur (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2020)
The collaboration of technology and media can have positive effects on teaching and learning. In modern teaching traditions, teachers must include technology into their teaching and must be able to select a suitable media so they can deliver lessons in the classroom effectively and can achieve the learning goal. This study is going to explore and elaborate the effectiveness of incorporating technology in learning process by using a media to get more engaging learning situation and to know its impacts to the students’ learning achievements, especially to their fluency and public speaking skill. To be specific, this study is trying to implement Video Blog (Vlog) as learning media in English speaking subject. The results of the observation show that, training students’ fluency and public speaking by implementing Vlog as learning media give positive impacts to the students. Vlog increases students’ encouragement in speaking. Vlog can provide fun and enjoyable learning process and it can build confidence.